2021
DOI: 10.3390/languages6010024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Task-Essential Training and Working Memory in Offline and Online Morphological Processing

Abstract: This study investigates the effects of task-essential training on offline and online processing of verbal morphology and explores how working memory (WM) modulates the effects of training. We compare a no-training control group to two training groups who completed a multisession task-essential training focused on Spanish verbal inflections related to person–number agreement and tense. Effects of training were evaluated using an offline aural interpretation task and an online self-paced reading (SPR) assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Lee and Doherty (2019) found that PI directed learners' attention to grammatical information on Spanish verbs marked for the passive voice and noted that learners' processing became more native-like after instruction. However, other studies have found mixed results or shown that training had no effect on online processing (Dracos & Henry, 2021;Ito & Wong, 2019;McManus & Marsden, 2017). For example, Dracos & Henry (2021) found that a PI-like training did not increase sensitivity to grammatical violations for Spanish subject and tense morphology.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
See 4 more Smart Citations
“…Lee and Doherty (2019) found that PI directed learners' attention to grammatical information on Spanish verbs marked for the passive voice and noted that learners' processing became more native-like after instruction. However, other studies have found mixed results or shown that training had no effect on online processing (Dracos & Henry, 2021;Ito & Wong, 2019;McManus & Marsden, 2017). For example, Dracos & Henry (2021) found that a PI-like training did not increase sensitivity to grammatical violations for Spanish subject and tense morphology.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
“…However, other studies have found mixed results or shown that training had no effect on online processing (Dracos & Henry, 2021;Ito & Wong, 2019;McManus & Marsden, 2017). For example, Dracos & Henry (2021) found that a PI-like training did not increase sensitivity to grammatical violations for Spanish subject and tense morphology. McManus and Marsden (2017) found no changes in online processing behavior for the French Imparfait when learners received training in the L2 only.…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
See 3 more Smart Citations